Dirac fermions induced in strained zigzag phosphorus nanotubes and their applications in field effect transistors. Issue 47 (22nd November 2016) - Yu, Sheng; Zhu, Hao; Eshun, Kwesi; Shi, Chen; Zeng, Min; Jiang, Kai; Li, Qiliang
Abstract : In this work, Dirac fermions have been obtained and engineered in one-dimensional (1D) zigzag phosphorus nanotubes (ZPNTs). Abstract : In this work, Dirac fermions have been obtained and engineered in one-dimensional (1D) zigzag phosphorus nanotubes (ZPNTs). We have performed a comprehensive first-principles computational study of the electronic properties of ZPNTs with various diameters. The results indicate that as the lattice parameter ( L c ) along the axial direction increases, ZPNTs undergo transitions from metal to semimetal and semimetal to semiconductor, whereas Dirac fermions appear at L c ranging from 3.90 Å to 4.10 Å. In particular, a field effect transistor (FET) based on 12-ZPNT (with 12 unit cells in the transverse direction) exhibits semiconductor behaviors with efficient gate-effect modulation at L c = 4.60 Å. However, only weak gate modulation is demonstrated when the nanotube becomes a semimetal at L c = 4.10 Å. This study indicates that ZPNTs are profoundly appealing for applications in strain sensors. Our findings pave the way for the development of high-performance strain-engineered electronics based on Dirac fermions in 1D materials.